Fintech for Social Impact: Evaluating the Role of Digital Finance in Poverty Alleviation - Ashari (Generate Digital Publishing, 2025)
Objective: This study aims to evaluate the contribution of fintech in reducing poverty through economic empowerment of low-income communities by utilizing digital technology. Research Design & Methods: This research uses a qualitative method with a systematic literature review approach to analyze fintech's contribution to reducing poverty through economic empowerment of low-income communities, utilizing data from previous literature studies. Findings: Fintech services such as micro-lending, micro-insurance, and mobile savings can empower disadvantaged individuals, but challenges such as digital infrastructure, low financial literacy, and social risks such as debt cycles need to be addressed to achieve optimal social impact. Implications & Recommendations: The importance of investing in digital infrastructure and financial literacy programs to improve the poor's understanding of fintech services and the need for collaboration between the government, fintech providers, and civil society organizations to formulate policies that support financial inclusion and protect consumers. Contribution & Value Added: This research contributes to illustrating how fintech can be an effective tool in reducing poverty, improving welfare, and supporting the achievement of the Sustainable Development Goals (SDGs).